Anastesi Inhalasi pada Tikus (Rattus Norvegicus) Menggunakan Eter dan Kloroform - Haryanto Haryanto; Alfani Zahrah Suci; Ahni Elena Aprilia; Ainun Mutia Putri; Sahratul Wilda; Harianti Harianti; Purnamasari Purnamasari (Inovasi Kesehatan Global, 2025)
This study aimed to compare the inhalation anesthetic profiles of ether and chloroform in white rats (Rattus norvegicus) using a modern pharmacological approach. Five healthy male rats (8–10 weeks old) were randomly divided into three groups: ether, chloroform, and control (ketoprofen). The main parameters observed were the onset time of loss of the righting reflex and the duration until its recovery. In theory, ether works by enhancing GABAergic transmission and inhibiting NMDA channels, thus having a slow but stable induction effect (IKAPI, 2009; Arqom, 2023). In contrast, chloroform works by stabilizing the neuronal membrane through activation of the K₂P TREK-1 channel and inhibition of Na⁺/Ca²⁺ currents, resulting in rapid induction with a short duration (Pavel et al., 2020). The experimental results support this theory: chloroform showed an average onset of 167.83 seconds and an anesthesia duration of 84.67 seconds, while ether had a slower onset (307.17 seconds) but a longer duration (169.33 seconds). The difference between the two was statistically significant (ANOVA, p<0.05). The coefficient of variation for chloroform was nearly four times higher than that of ether, indicating that ether provides a more consistent anesthetic effect across individuals. These findings are consistent with previous studies, such as Fathiyah & Anretha's (2023) report on the variability of chloroform effects and the results of in vivo amethyst anesthesia studies (Aprira, 2022; Genta et al., 2021). Overall, ether is more suitable for medium-term procedures requiring stable anesthesia, while chloroform is suitable for short interventions requiring rapid induction. This study emphasizes the importance of controlled inhalation environments, adequate sample sizes, and chamber standardization to enhance the external validity of the results.